Characterization of physical, chemical and microstructure properties in the soft clay soil of the paddy field area - Muhammad Rendana; Wan Mohd Razi Idris; Sahibin Abdul Rahim; Zulfahmi Ali Rahman; Tukimat Lihan (Sebelas Maret University, 2021)
The soft clay soil has been categorized as infertile soil. The occurrence of soft clay soil in paddy field areas can decline soil quality and rice production. Therefore, to find the best technique for amending this soil, this study aimed to analyze the physical, chemical, and microstructure properties of the soft clay soil in the paddy field area. The soft clay soil samples were collected from two paddy blocks in Kedah, Malaysia. The physical and chemical properties of the soil were determined using the standard method in the laboratory. The microstructure properties were analyzed using Zeiss SUPRA 55VP microscopes. The results found that the soft clay soil was composed of silt – clay (> 90%) with the texture of silty clay. The soft clay soil was characterized by low values of organic matter (2.63-3.42%), pH (3.32-3.69), cation exchange capacity (6.89-8.72 cmolc kg-1), available P (0.14-0.41 mg kg-1), aggregate stability (16.53-17.78%), and hydraulic conductivity (0.17 cm hr-1). In contrast, it indicated high values of soil water content (42.24-43.21%), and exchangeable Na+ ions (2.48-2.50 cmolc kg-1). In addition, the analysis of heavy metals content revealed that their concentrations were below the critical level in the soil. The soft clay soil was largely governed by kaolinite minerals, and it had less compact structures with many large voids among soil aggregates. In conclusion, the quality of soft clay soil in the study area was poor with low physical and chemical parameters. The quality of the soil could be improved by the addition of soil amendments such as zeolite, cement, and other additive materials to absorb the excess water in the soil and increase the soil strength.